Kisah Sukses Inovasi Marketing from Commodity Becomes Solution (Studi Kasus Tentang PT Holcim Indonesia Tbk) - Handy Martinus (Humaniora, 2012)
Cement is a strategic commodity. Indonesia as a developing country continues, cement becomes something absolute. Particularly, in the next few years, infrastructure development continues announced. To it, we need to anticipate the occurrence of scarcity (shortage) of cement to meet the needs in the country in the next couple years. Fears of a shortage of cement in the country are quite groundless. Currently installed production capacity of the national cement industry around 47.5 million tons per year, spreads over nine locations in Indonesia. Meanwhile, the average utilization rate of production capacity cement plant reaches between 80% -85% or about 38-40 million per year. Meanwhile, the current level of cement consumption reached about 33 million tons (still a surplus of about 5-7 million tons). The problem is, if the shortage is met from imports, it could damage the domestic cement industry. Therefore, to meet the interests of industry and consumers, the best way is the expansion of the new plant. And to support the expansion of the factory in the country, clearly requires a major investment. Based on the assumptions above, Holcim as a newbie in the national cement market, which previously bought cement Cibinong also takes part in the national market. Now, Holcim is not half-hearted continuously expanding its new factory in Tuban to increase the strength of its two plants that are already running. A series of innovations in marketing activities are carried out, ie not just treating cement as a commodity but rather providing a range of service solutions to users via the outlet solution that provides aid earthquake resistant building design, material supply multi-brand, as well as a series of cooperation in the process of financing by establishing cooperation to the bank.